Analisis Efisiensi Waktu Bongkar Muat Semen pada MV. Dian Prosperity - Moh. Fatrit Emboma; Mudiyanto Mudiyanto; Dedy Kristiawan (Port Management and Maritime Administration Journal, 2026)
This study was conducted in response to the suboptimal efficiency of cement unloading operations on board MV. Dian Prosperity, which has contributed to extended port stay and increased operational costs. The study aims to identify the factors contributing to unloading delays, analyze the efficiency of unloading operations based on actual voyage data, and formulate strategies to improve the vessel's operational efficiency. This research employed a qualitative method with a descriptive approach. Data were collected through field observations, interviews with the Master, deck officers, and crew members, as well as documentation studies involving voyage records, logbooks, Standard Operating Procedures (SOPs), and other operational documents. Data analysis was carried out through data reduction, data presentation, triangulation, interpretation, and conclusion drawing. The findings indicate that the cement unloading operations on MV. Dian Prosperity have not been performed efficiently or consistently. Of the 18 voyages analyzed, most experienced delays caused by valve leakage, pressure drop, delayed readiness of the receiving silo, as well as inadequate operational coordination and inconsistent implementation of Standard Operating Procedures. Therefore, operational efficiency can be improved through preventive maintenance of the pneumatic unloading system, stronger coordination between the vessel and port authorities, adequate availability of critical spare parts, and enhanced crew competence in handling operational disruptions, thereby enabling the unloading process to be carried out more effectively, efficiently, and sustainably.